The effects of mergers on the trade component of the balance of payments: The British evidence - A. Pouris (South African Journal of Business Management, 1987)
This paper investigates empirically the effects of mergers within the British manufacturing industry on the trade component of the balance of payments. The effects of different merger rates over time on the trade component of the balance of payments are examined for the period 1880-1969. The effects of different merger rates over industry on the import/export performance of those industries are examined for the period 1969-1983. The results show that mergers had an adverse effect on the trade balance over the period 1880-1969 and that mergers did not determine the industries' performance over the period 1969-1983. It is argued that the neutral effects during the most recent period, are the result (actual and deterrent) of the Monopolies and Mergers Act 1965 and not due to similar merger movements in the main trade partner countries.
Keywords: 650